2016
DOI: 10.1186/s12302-016-0092-7
|View full text |Cite
|
Sign up to set email alerts
|

Since 2015 the SinoGerman research project SIGN supports water quality improvement in the Taihu region, China

Abstract: The Taihu (Tai lake) region is one of the most economically prospering areas of China. Due to its location within this district of high anthropogenic activities, Taihu represents a drastic example of water pollution with nutrients (nitrogen, phosphate), organic contaminants and heavy metals. High nutrient levels combined with very shallow water create large eutrophication problems, threatening the drinking water supply of the surrounding cities. Within the international research project SIGN (SinoGerman Water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The loss of phosphorus (P) from agricultural soils has been identified as one of the main causes of eutrophication of lakes in the lower reaches of the Yangtze River in southern China [1]. Statistics have shown that major lakes and reservoirs in this area were eutrophic and mesotrophic [2][3][4], and the Yangtze River Delta region accounted for 17% of the 10 Tg annual increase in soil P around the world [2]. In soil, colloidal P (P coll ) is the P fraction bound to colloids [5].…”
Section: Introductionmentioning
confidence: 99%
“…The loss of phosphorus (P) from agricultural soils has been identified as one of the main causes of eutrophication of lakes in the lower reaches of the Yangtze River in southern China [1]. Statistics have shown that major lakes and reservoirs in this area were eutrophic and mesotrophic [2][3][4], and the Yangtze River Delta region accounted for 17% of the 10 Tg annual increase in soil P around the world [2]. In soil, colloidal P (P coll ) is the P fraction bound to colloids [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrological problems usually involve huge amounts of data, complicated or temporarily unknown mechanisms, and nonlinear spatial and temporal distribution (Schmidt et al 2016). Artificial neural networks (ANNs) can be used to model and solve problems when constructing hydrological models.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of phosphorus (P) from agricultural soils has been identified as one of the main causes of eutrophication of lakes in the lower reaches of the Yangtze River in southern China [1]. Statistics have shown that major lakes and reservoirs in this area were eutrophic and mesotrophic [2][3][4], and the Yangtze River Delta region accounted for 17% of the 10 Tg annual increase in soil P around the world [2]. In soil, colloidal P (P coll ) is the P fraction bound to colloids [5].…”
Section: Introductionmentioning
confidence: 99%